STUDI TENTANG KEBIJAKAN DALAM PELAKSANAAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DI SEKOLAH LUAR BIASA NEGERI (SLBN) TENGGARONG KABUPATEN KUTAI KARTANEGARA - novira cahya wulan Sari (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2016)
The Child With Special Needs (ADD/ADHD) as Indonesian, has a right to access education. Education is everyone need, included The Child With Special Needs (ADD/ADHD). They need special service in education which suitable with their characteristics. SLBN Tenggarong which located in Kutai Kartanegara is a special school build for them. The research found that Inklusi’s school has not reserved in each district, less of teacher has special needs like therapy room, deafaid and others. Hopely, the policy can help them to have self-reliance to survive in society, self-defence for their self, so that people will not see them cynically in social life, know their talent, and there are some observers in Kutai Kartanegara who care about them.